PRELIMINARY STUDY ON BIOSYNTHESIS, ISOLATION AND PURIFICATION OF L-35S-METHIONINE LABELLED COMPOUNDS - Oekar, Nanny Kartini (Indonesian Journal of Pharmacy, 2002)
The preliminary study of biosynthesis sulphur-35 amino acids labelled compounds has been done using wild strain of Baker's yeast Saccharomyces cerevisiae as producer mycroorganism and the solution of Na35SO4 (45 mCi/60 L) as tracer source was added into the salt media, in which the incorporation of S-35 radioisotope to the yeast cells was synthesized. Maximum incorporation of 93,5 % was obtained after 10 hours incubation at 30 C. Hydrolysis was carried out using HCl 6N and heating at 110 C for 18 hours to destroy the yeast cells, therefore L-35-methionine and the other amino acids would dissolve in the solution. Hydrolisate isolation was exhibited using two step of coloumn chromatographic using Dowex-cation exchanger resin as stationary phase and the demineralized steril water containing 0, 1 % -mercapto ethanol (ME) and the mixing of water: HCl 4N which contains 0, 1% ME as mobile phase. The ratio volume of these both mobile phases were gradually adjusted. Purified amino acids the was analysized using paper chromatography method. The result shows that the 7th fraction of eluate contained L.35S-methionine biosynthesized by yeast Saccharomyces cerevisiae, that had high radiochemical purity (100 %) and the radioactive concentration of L-35S-methionine was 28 mCi/ml.Key-words: amino acids, biosynthesis, sulphur-35, L-35-S-methionine. Pertanian Kerjasama Dengan Kanwil Deptan dan Disbun Sumbar, Riau dan Jambi di Bukit Tinggi 15 - 17